2022
DOI: 10.1097/tp.0000000000004088
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived Cell-free DNA Shows High Sensitivity for the Diagnosis of Pancreas Graft Rejection in Simultaneous Pancreas-kidney Transplantation

Abstract: Background. Pancreas graft status in simultaneous pancreas-kidney transplant (SPKTx) is currently assessed by nonspecific biochemical markers, typically amylase or lipase. Identifying a noninvasive biomarker with good sensitivity in detecting early pancreas graft rejection could improve SPKTx management. Methods. Here, we developed a pilot study to explore donor-derived cell-free DNA (dd-cfDNA) performance in predicting biopsy-proven acute rejection (P-BPAR) of the pancreas graft in a cohort of 36 SPKTx reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…These results correlate with another recent study in which, exploring a gene set to evaluate the expression of ABMR in pancreas graft biopsy, there was no correlation between the presence of DSA and ABMR gene expression (44). Finally, we have recently reported that donor-derived cfDNA was increased in patients with DSA despite the absence of signs of ABMR in graft biopsy (45). Altogether, these studies highlight that histological ABMR may be underdiagnosed in pancreas transplantation, and is important to design larger studies in patients with pancreas ABMR aiming at exploring the molecular and genetic biomarkers, and more in depth functional analysis of peripheral blood mononuclear cells.…”
Section: Discussionsupporting
confidence: 90%
“…These results correlate with another recent study in which, exploring a gene set to evaluate the expression of ABMR in pancreas graft biopsy, there was no correlation between the presence of DSA and ABMR gene expression (44). Finally, we have recently reported that donor-derived cfDNA was increased in patients with DSA despite the absence of signs of ABMR in graft biopsy (45). Altogether, these studies highlight that histological ABMR may be underdiagnosed in pancreas transplantation, and is important to design larger studies in patients with pancreas ABMR aiming at exploring the molecular and genetic biomarkers, and more in depth functional analysis of peripheral blood mononuclear cells.…”
Section: Discussionsupporting
confidence: 90%
“…(Oellerich et al, 2021). Dd-cfDNA detects rejection also in liver (Schuetz et al, 2017;Levitsky et al, 2022), heart (Snyder et al, 2011;De Vlaminck et al, 2014;Khush et al, 2019;Richmond et al, 2020;Agbor-Enoh et al, 2021a;Sorbini et al, 2021), lung (Rosenheck et al, 2022a) and simultaneous pancreas-kidney (Ventura-Aguiar et al, 2022) transplant patients with good accuracy (Table 2). Dd-cfDNA fraction was also significantly elevated for CLAD (De Vlaminck et al, 2015).…”
Section: Clinical Validity Of Donor-derived Cell-free Dna In Transpla...mentioning
confidence: 99%
“…Analyzing dd-cfDNA has shown great potential as a biomarker for monitoring the allograft health, where an increase of the dd-cfDNA fraction in the recipient's bloodstream will indicate organ damage [2,[8][9][10][11][12]. As a noninvasive marker for organ health, dd-cfDNA testing has been applied for various organs [3,6], including the heart [13][14][15][16][17][18][19][20][21][22], kidney [5,[23][24][25][26][27][28][29], liver [11,29], lung [30][31][32], and pancreas and simultaneously pancreas-kidney transplantation [33].…”
Section: Introductionmentioning
confidence: 99%